Can taxes tame the banks? evidence from the European bank levies - Devereux, M; Johannesen, N; Vella, J (Oxford University Press, 2019)
Following the 2007-2008 financial crisis, a large number of countries introduced levies on bank borrowing intended to reduce risk in the financial sector. This paper studies the behavioral responses to bank levies and finds that banks exposed to levies increased their reliance on equity funding, but at the same time increased the risk of their assets; banks shifted risk from the liability side of their balance sheets to the asset side, which mitigated the impact of government intervention. Our analysis also shows that any reduction in total risk was concentrated among banks that pose no or little threat to financial stability.